2021
DOI: 10.1186/s12957-021-02445-6
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram model for predicting prognosis of obstructive colorectal cancer

Abstract: Background The prognosis of obstructive colorectal cancer (oCRC) is worse than that of nonobstructive colorectal cancer. However, no previous study has established an individualized prediction model for the prognosis of patients with oCRC. We aimed to screen the factors that affect the prognosis of oCRC and to use these findings to establish a nomogram model that predicts the individual prognosis of patients with oCRC. Methods This retrospective st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 43 publications
(48 reference statements)
0
28
0
Order By: Relevance
“…We also analyzed the correlation between the patient's serum in terms of total protein, albumin and other laboratory indicators and tumor development, and finally found that low protein levels may facilitate the growth and metastasis of tumor cells, which may ne beneficial to predict the probability of LNM (34). In a retrospective study of 207 cancer patients, Adam et al (24) found that positive lymph nodes are significantly correlated with low albumin levels, and it was concluded that cancer patients are usually accompanied by hypoproteinemia and the subsequent production of ascites and tissue oedema may cause migration of tumor cells, leading to the development of LNM. A related discussion has been found in other studies (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…We also analyzed the correlation between the patient's serum in terms of total protein, albumin and other laboratory indicators and tumor development, and finally found that low protein levels may facilitate the growth and metastasis of tumor cells, which may ne beneficial to predict the probability of LNM (34). In a retrospective study of 207 cancer patients, Adam et al (24) found that positive lymph nodes are significantly correlated with low albumin levels, and it was concluded that cancer patients are usually accompanied by hypoproteinemia and the subsequent production of ascites and tissue oedema may cause migration of tumor cells, leading to the development of LNM. A related discussion has been found in other studies (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…A nomogram risk prediction model for colorectal cancer patients has been developed, however lacking data on its pathological type and on the prognosis of lymph node positive patients [21][22][23]. Moreover, these reports have not distinguished RSJ from coloretal cancer [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms were widely used for cancer prognosis. Based on age, gender, tumor (T), node (N), metastasis (M) and risk score, a nomogram was constructed using "RMS" package in R. Calibration curves was used to visually predict deviations between actual and predicted survival [17].…”
Section: Construction Of the Nomogrammentioning
confidence: 99%